Aplikasi Augmented Reality Jurusan Teknologi Informasi Universitas Udayana (AR-TI) - Dewi, Desak Ayu Sista; Putra, I Ketut Gede Darma; Bayupati, I Putu Agung (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Augmented Reality is a technology that combines object 2-dimensional and 3-dimensional into a real envireonment in real time. Department of Information Technology is an eight years old department that has basic amenity such as a building with several rooms where the learning processes take place. Application of Augmented Reality technology used in the design of applications Augmented Reality or AR Department of Information Technology-IT is designed to be user friendly. The design uses a marker of the rupiah currency aims to simplify the user to get information anywhere and anytime because it is universal. The performance of AR-IT application that users use the rupiah currency scanning the marker using Android smartphone then the application can display 3-dimensional objects and voice narration about Udayana University Information Technology building.